DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON APPLICATIONS ARTICULATE STORYLINE 3 HUMAN COORDINATION SYSTEM MATERIAL - Nurul Fadhilah H.M; Andi Tenri Ola Rivai; Syamsul Syamsul (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This research is included in the type of research and development or Research and Development (R&D) based on the ADDIE development model which consists of five steps, namely Analyze, Design, Develop, Implement and Evaluate. This study aims to develop learning media, determine the level of validity, level of practicality and level of effectiveness of media. This research was conducted at SMA Negeri 2 Takalar class XI Science 1 which amounted to 30 students. Media validity of 3.80 with very valid category. The practicality of the media obtained through teacher responses is 95.31% and student responses are 85.18% with very practical categories. Of the 30 total students, 27 of them obtained scores that were in accordance with the KKM target (90%) and 3 of them obtained scores that did not meet the KKM target (10%). The pretest score of students obtained is 28.13 while the posttest value is 81.33, so that the average N-gain score obtained by students is 0.72 and is in the category (0.7 g ≤ 1), it can be said that the increase in student learning outcomes is high.